Analysis and understanding the (MIS & FIS) report of Padakhep Manabik Unnayan Kendra, LEAP program - Sohel, Jobayer Al Mahmud (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2023.